Longshot enables accurate variant calling in diploid genomes from single-molecule long read sequencing - Peter Edge (Nature Portfolio, 2019)
Single-molecule sequencing (SMS) such as Pacific Biosciences and Oxford Nanopore generate long reads with high error rate. Here, the authors develop Longshot, a computational method that detects and phases single nucleotide variants (SNV) in diploid genomes using SMS data.